PENGELOLAAN ZAKAT SEBAGAI BENTUK PENEGAKAN HAM DALAM MENINGKATKAN KESEJAHTERAAN RAKYAT - 'Ulya, Zaki (al-'adalah, 2015)
Abstract: Management of Zakat as a Form Human Right Enforcement in Improving People’s Welfare. Poverty, income inequality, poor health and education services as well as high unemployment rate are some indicators showing that there are many violations of people’s rights. Implementation of zakat management set out in the legislation is one of the government’s efforts in tackling economic inequalities in society so that the basic rights of the people in economics can be fulfilled. Obstacles encountered in the management of zakat in general are in the mechanism of distribution of zakat since the charity is based on some legislation that put zakat as regional income resulting in a very bureaucratic withdrawal prcess of funds from the charity accountant area. As the result, it hampers the distribution of zakat hence economic rights of the people cannot be optimally fulfilled.Abstrak: Pengelolaan Zakat Sebagai Bentuk Penegakan HAM dalam Meningkatkan Kesejahteraan Rakyat. Fenomena kemiskinan, distribusi pendapatan nasional yang kurang merata, buruknya layanan kesehatan dan pendidikan, serta masih tingginya angka pengangguran, dapatlah dipakai sebagai indikator masih banyaknya pelanggaran terhadap hak asasi rakyat. Pelaksanaan pengelolaan zakat yang telah diatur dalam peraturan perundang-undangan merupakan upaya pemerintah dalam menanggulangi kesenjangan ekonomi dalam masyarakat, sehingga hak dasar manusia di bidang ekonomi menjadi tercukupi. Kendala yang dihadapi dalam pengelolaan zakat pada umumnya ada pada mekanisme pendistribusian zakat. Di mana zakat berdasarkan beberapa peraturan perundangan menempatkan sebagai PAD sehingga dalam penarikan dana zakat dari akuntan daerah sangat birokratis. Akibatnya pendistribusian zakat pun menjadi terhambat, dan hak ekonomi rakyat belum dapat terpenuhi secara optimal.